Nigerian libraries and indeginous conflict management:past and current isssues in library and information science towards peace and development (2010)
Conflict management is an issue that concerns everyone and has implications for fututre existence and co- existence of people. Where conflicts abound, resolution of such is of importance to prevent escalation of the conflicts and resultant choas. The role of public, research, acedemic and special libraries in indigenous conflict resolution is explored in this paper. A study of 15 (fifteen) libraries was undertaken, and thier roles in conflict resolution examined. The challenges faced and successes recorded are reported. However, the study also majors on the activities of Conflict Awareness and Prevention Initiatives (CAPI) Research libraries, Ibadan whose unique services provide unique information towards global peace and development. Recommendations are made on how better provisions can be made for the libraries using new information and communication technologies and even indigenous methods (Native intelligence) to build peace in various communities where conflicts arise or are likely to arise